Dialogando com o Tribunal de Contas do estado do Rio Grande do Sul: análise das referências sobre estado, gestão e financiamento nas reportagens do TCE-RS - Silva, Everaldo Silveira da (2019)
Transparency in the use of public resources can be taken as an instrument of public participation and control of what is public by showing citizens in a clear and objective manner the foundations of the democratic rule of law. The subject of this dissertation refers to the role of the Tribunal de Contas do Estado as a disseminating body of technical information on the funding of education in Rio Grande do Sul, as well as the understandings of this Court in the field of Management and Funding of Education. The research seeks to analyze what is the view of the Tribunal de Contas do Estado (TCE-RS) about the publications referring to the application of public resources destined to education, as well as, which were the categories that TCE-RS disposed to address in its reports in the from 2011 to 2018. It should be noted that this public oversight body provides the company with access to information on expenditures, allowing it to contribute to the Tribunal's purpose in order to promote social control, since it only controls something who has the knowledge to do so. To address the research problem, a study with bibliographic references was conducted by authors such as: a) Lessard (2016), Souza (2006), Mainardes (2017) and Dale (2010), in order to discuss educational policies; b) Farenzena (2006), to discuss education funding; and c) Bobbio (1987) and Nobrega (2018), to reason the concept of state. It was also sought, with the help of materials already existing in current legislation, articles and dissertations, to map and analyze what is already discussed about the paths and processes of funding public basic education in the reality of Rio Grande do Sul. This research has a tabulation of the data, as well as a qualitative and quantitative analysis of them. It should be noted that the study also has a probabilistic sampling in relation to users' access to the court's website. The guiding source for the investigation is the Tribunal de Contas do Rio Grande do Sul database, which provided access to various indicators on public expenditure related to resource management. Based on the data analyzed, it was concluded that the TCE is a very important tool in the hands of the population as it allows access to public management information and gives users the possibility to have their information through this open channel, posted and be able to charge managers to account for public spending.